PENGARUH SUPERVISI DAN SERTIFIKASI TERHADAP MOTIVASI KERJA DAN KINERJA GURU SEKOLAH MENENGAH KEJURUAN DI KECAMATAN ADIWERNA KABUPATEN TEGAL - Ery Suryanti (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2016)
The purpose of this reseach is the influence supervision and sertification to the work of motivation and to teacher’s performance of vocational high school in adiwerna subdistrict Tegal regency. This research uses descriptive method. The supervition effect (X1), sertification (X2) as independent variable and work motivation (Y1), teacher’s performance (Y2) as dependent variable. The technique of sampling uses proportional random sampling with number of population 211 people and for sample 68 people. The result showed that : 1) the supervition takes effect to teacher’s wo the supervition takes effect to teacher’s work motivation of vocational high school in adiwerna subdisrtict Tegal regency. 2) the sertification takes effect to teacher’s work motivation of vocational high school in Adiwerna subdistrict Tegal regency. 3) the supervition doesn’t takes effect to teacher’s work motivation of vocational high school in Adiwerna subdisrtict Tegal regency. 4) the sertification takes effect to teacher’s performance of vocational high school in Adiwerna subdisrtict Tegal regency. 5) the work motivation takes effect to teacher’s performance of vocational high school in Adiwerna subdisrtict Tegal regency. Keywords : Supervition, Sertification, Work motivation, Performance